First Genome Sequence of Leptospira interrogans Serovar Pomona, Isolated from a Bovine Abortion - Varni, Vanina Delia; Koval, Ariel; Nagel, Ariel Gaston; Ruybal, Paula; Caimi, Karina Cynthia; Amadio, Ariel F. (2017)
Leptospirosis is a widespread zoonosis and a re-emergent disease of global distribution with major relevance in veterinary pro- duction. Here, we report the whole-genome sequence of Leptospira interrogans serovar Pomona strain AKRFB, isolated from a bovine abortion during a leptospirosis outbreak in Argentina